Three-Level Model оf the National Innovation System оf Ukraine - Tsybulov, P.M. (Science and Innovation, 2024)
Introduction. For National Innovation Systems (NIS) playing an important role in building the modern economies, the development and improvement of the NIS model of Ukraine is an urgent task. Problem Statement. There are many models of NIS in the world but they cannot be used by Ukraine, since they do not take into account the specifics of its socio-economic development. Purpose. To develop a model for the NIS of Ukraine containing a necessary and sufficient set of subsystems, elements, and links between them and taking into account the specific features of the socioeconomic development of Ukraine. Materials and methods. The scholarly research publications of domestic and foreign researchers, legal acts, methods of analysis and synthesis have been used in the work. Results. Based on system approach, a comprehensive NIS model has been obtained. It covers the four stages of the innovation process and considers the impact of national and international innovation community on them. Conclusions. A three-level model of the NIS of Ukraine has been proposed. It has necessary and sufficient number of elements and connections between them for the implementation of the NIS functions. The model can be used as a tool for preparing strategic decisions to optimize the NIS of Ukraine.